Long-run relationship between crop-biodiversity and cereal production under the CAP reform: evidence from Italian regions - Elisa Gatto; Guido Signorino (European Regional Science Association (ERSA), 2011)
Biodiversity has a prominent role in defining and preserving ecosystem well-being; the analysis of biodiversity effects on agricultural production is well documented. The paper offers empirical evidence on the role of intra-species biodiversity in sustaining cereal production within Italian regions, covering a time span (1989-2007) which accounts for the important CAP policy reforms. A Cobb-Douglas production function that includes both biodiversity and subsidies as control variables is estimated for 20 Italian regions, controlling for both cross-sectional heterogeneity and the dynamic structure of agricultural production. Different estimation methods are compared, including Mean Group and Pooled Mean Group estimators which allow for the possibility of potential non stationarity of the series and heterogeneous parameters across-groups. We find clear evidence of significant long-run relationships between biodiversity and cereal production; moreover, the evidence on the role of PAC intervention measures is less clear-cut, showing a potentially negative effect on production along the period under analysis that can be attributed to the aforementioned policy shift.
Keywords: 330